Standing genetic variation as a potential mechanism of novel cave phenotype evolution in the freshwater isopod, Asellus aquaticus. Issue 2 (8th February 2023) - Rodas, Lizet R.; Sarbu, Serban M.; Bancila, Raluca; Price, Devon; Fišer, Žiga; Protas, Meredith
Abstract: Novel phenotypes can come about through a variety of mechanisms including standing genetic variation from a founding population. Cave animals are an excellent system in which to study the evolution of novel phenotypes such as loss of pigmentation and eyes. Asellus aquaticus is a freshwater isopod crustacean found in Europe and has both a surface and a cave ecomorph which vary in multiple phenotypic traits. An orange eye phenotype was previously revealed by F2 crosses and backcrosses to the cave parent within two examined Slovenian cave populations. Complete loss of pigmentation, both in eye and body, is epistatic to the orange eye phenotype and therefore the orange eye phenotype is hidden within the cave populations. Our goal was to investigate the origin of the orange eye alleles within the Slovenian cave populations by examining A. aquaticus individuals from Slovenian and Romanian surface populations and Asellus aquaticus infernus individuals from a Romanian cave population. We found orange eye individuals present in lab raised surface populations of A. aquaticus from both Slovenia and Romania. Using a mapping approach with crosses between individuals of two surface populations, we found that the region known to be responsible for the orange eye phenotype within the two previously examined Slovenian cave populations was also responsible within both the Slovenian and the Romanian surface populations. Complementation crosses between orange eye Slovenian and orange eye Romanian surface individuals suggest that the same gene is responsible for the orange eye phenotype in both surface populations. Additionally, we observed a low frequency phenotype of eye loss in crosses generated between the two surface populations and also in the Romanian surface population. Finally, in a cave population from Romania, A. aquaticus infernus, we found that the same region is also responsible for the orange eye phenotype as the Slovenian cave populations and the Slovenian and Romanian surface populations. Therefore, we present evidence that variation present in the cave populations could originate from standing variation present in the surface populations and/or transgressive hybridization of different surface phylogenetic lineages rather than de novo mutations. Abstract : An orange eye phenotype, hidden within cave populations (masked by absence of pigment), was uncovered through crossing cave populations with surface populations. A similar orange eye phenotype can be found within surface populations suggesting that orange alleles within the cave populations originated from standing variation in the founding surface population.